Die regsetiese implikasies van buite-egtelikheid - Plessis, W. du (Koers, 1985)
In this article the author deals with the ethico-judiciary aspects of illegitimacy. Because of the stigma clinging to the illegitimate child, certain constraints have been imposed from the side of the authorities as well. These are then examined. Following a definition of the concept, the results of illegitimacy are considered in terms of the status of the child, its maintenance, inheritance, as well as certain non-juridical factors such as social, biological, religious and ethical factors. The important question of attitudes towards illegitimacy is then considered, with reference to changed attitudes in certain overseas countries, such as America, the Scandinavian countries, Britain, Italy, the Netherlands, and finally South Africa. It emerges then that a more sympathetic attitude towards both the child and the mother is evolving, in South Africa too. The changed attitudes of the community, however, do not suspend the constraints imposed upon the child by the law. The author feels, however, that as a result of the state's involvement with the problem of illegitimacy, the problem has shifted from the ethical to the field of the state, and the state now has to act to redress the balance. The author is of the opinion, further, that legislation should be developed to eliminate the legal constraints - if a sanction needs to be imposed, it should be imposed on the parents and not on the child. It is therefore noted with satisfaction that the Law Commission has proposed a Draft Bill in this regard to remove the legal constraints upon the illegitimate child .